Feature - Based Approach to Automatic Fixturing System Planning For Uniform Polyhedra Workpiece - Zghair, Haidir Raheem; Zghair, Haidir Raheem; Zghair, Haidir Raheem; Zghair, Haidir Raheem; Yaqoub, Zaid Hikmat; Barzan, Amjad (Al-Khwarizmi Engineering Journal, 2019)
This paper demonstrates the design of an algorithm to represent the design stages of fixturing system that serve in increasing the flexibility and automation of fixturing system planning for uniform polyhedral part. This system requires building a manufacturing feature recognition algorithm to present or describe inputs such as (configuration of workpiece) and built database system to represents (production plan and fixturing system exiting) to this algorithm. Also knowledge – base system was building or developed to find the best fixturing analysis (workpiece setup, constraints of workpiece and arrangement the contact on this workpiece) to workpiece.